THE USING OF INQUIRY METHOD WITH CONCRETE OBJECT MEDIA IN IMPROVING NATURAL SCIENCE LEARNING ABOUT LIGHT AT THE FIFTH GRADE STUDENTS OF SDN 1 KALIGOWONG IN THE ACADEMIC YEAR OF 2014/2015 - Rizqina, Teza (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstrak: The Using of Inquiry Method with Concrete Object Media in Improving Natural Science Learning about Light at the Fifth Grade Students of SDN 1 Kaligowong in the Academic Year of 2014/2015. The objectives of this research are to describe steps in using inquiry method with concrete object media, to improve natural science learning and to describe problems and solutions in using inquiry method with concrete object media. This collaborative Classroom Action Research (CAR) conducted in three cycles, with each cycle consisting of planning, implementation, observation, and reflection. The subjects 23 students. The result showed there are improving learning natural science about by applying  inquiry methods with concrete object media. The conclusion of this research is the using of inquiry method with concrete object media carried out with appropriate steps can improve natural science learning about light at the fifth grade students of SDN 1 Kaligowong in the academic year of 2014/2015.  Keyword : Inquiry Methods, Konkret Media, Learning, Natural Science.